Prescribing of Potentially Inappropriate Medications to ElderlyPeople by Medical Specialists in Isfahan, Iran: Inappropriate prescription - Amir Houshang Zargarzadeh; Parisa Mirmoghtadaei; Kourosh Sadeghi (Iranian Journal of Pharmaceutical Sciences, 2008)
The goal of this study is to identify the types of potentially inappropriate drugs prescribed by the medical specialists of Isfahan province to elderly patients. A number of 31,254 randomly selected prescriptions from medical specialists of Isfahan province were reviewed for elderly patients who were insured by the Social Security Organization. Three thousand and seven prescriptions were identified and Beers’Criteria was applied to figure out the type of inappropriate medications. The study concluded 49% males and 51% females. Sixty one percent of patients were 65-74 years old and 39% older than 74 years old. Of all the prescriptions reviewed, 24.4% contained inappropriate medications. The ten most common medications detected in the prescriptions were: Naproxen (18.4%), fluoxetine (8.3%), clidinium C (7.2%),indomethacin (7.2%), chlordiazepoxide (5.8%), doxepin (4.76%), dipyridamole (4.4%), amitriptyline (4.27%), methocarbamol (4.15%) and piroxicam (3.88%). Theresults are comparable to what has been reported in the literature. This is also inaccordance with the national drug consumption as NSAIDs are heavily usedthroughout Iran. Due to the extent of inappropriateness of medicine use in the elderly population, we need to define a strategy to curtail this problem including educational classes for physicians and launching national geriatrics residency programs.